Strategic Clinical Supervision: Redefining Principal Leadership in Enhancing Teacher Professionalism - Anisah Aruan; Inom Nasution (Al-Qalam Institue, 2026)
This study aims to examine the management of principals’ clinical supervision in improving teachers’ professional competence, particularly within the dimensions of educational management: planning, organizing, implementing, supervising, and evaluating. The research employs a qualitative approach with a phenomenological case study design. Data were collected through in-depth interviews and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and technique triangulation. The findings reveal that clinical supervision is systematically planned through structured programs, needs-based target setting, and pre-observation communication. In the organizing and implementation stages, supervision is conducted collaboratively despite constraints such as limited time and competing managerial responsibilities. Continuous supervision and evaluation are carried out through classroom observations, reflective dialogues, and ongoing professional guidance tailored to teachers’ needs. Follow-up actions emphasize sustainable professional development and instructional improvement. These findings imply that integrated and reflective clinical supervision management strengthens the principal’s role as an instructional leader and significantly enhances teachers’ professional competence. Effective supervision grounded in educational management dimensions contributes to sustainable school improvement and adaptive post-pandemic learning practices.